Sequential gold-catalyzed carbene transfer/ring closure: oxidative cyclization of β-(2-Alkynylphenyl)-α,β-ynones to indenofuranones - Rode, Navnath; Adak, Tapas; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2018)
β-(2-Alkynylphenyl)-α,β-ynones undergo a gold-catalyzed oxidative two-fold cyclization in the presence of N-oxides to give 1,3-disubstituted-8H-indeno[1,2-c]furan-8-ones in good yields. This cascade process is triggered by a selective oxygen transfer from an N-oxide onto the gold-activated alkynone to generate a α-dioxocarbene intermediate which, via carbene transfer across the remaining alkyne moiety and subsequent cyclization through nucleophilic attack by a carbonyl oxygen, achieves the construction of 1,3-disubstituted fused polycyclic furans.